우리나라 초등학교·중학교·고등학교에서 근무하는 교사와 직원의 운동장 종류에 대한 인식 조사 비교 연구 - 장석원(Seog-Won Chang) (Weed & turfgrass science, 2019)
우리나라 학교운동장은 주로 3가지 종류(천연잔디, 인조잔디, 맨땅)로 조성되어 운영되고 있다. 학교 운동장은 조성된 피복물의 종류에 따라 장점과 단점이 다르기 때문에 구성원의 만족도 차이가 있을 수 있다. 최근 전국적으로 다양한이유로 인해 운동장 종류를 바꾸는 학교가 늘어나고 있다. 따라서 학교 구성원의 운동장에 대한 만족도를 파악하는 것은 그들이 운동장 종류를 선정하는 의사결정 과정에서 영향을 미칠 수 있다는 점에서 매우 중요하다. 하지만 이에 관한연구는 이루어진 바 없다. 본 자료는 천연잔디운동장, 인조잔디운동장, 맨땅운동장을 운영하고 있는 390개 학교(운동장별 각 130개 학교)에 설문지를 보낸 후 운동장 담당자로부터 회신 받은 자료(천연 27개, 인조 23개, 맨땅 29개 학교)를 근거로 작성, 분석한 결과이다. 초등학교 ·중학교 ·고등학교 구성원인 학생, 직원, 학부모의 운동장 종류에 대한 만족도는천연잔디>인조잔디>맨땅운동장 순서로 높아 같은 의견을 보였다. 교사와 직원은 천연잔디운동장의 가장 큰 장점으로학생들에게 안전하다는 점(83.8%)과 자연친화적인 환경(90.9%), 가장 큰 단점으로 제한된 사용(71.1%)과 어려운 관리(63.6%)를 각각 꼽아 다른 의견을 보였다. 교사와 직원은 인조잔디운동장의 가장 큰 장점으로 연중 사용 가능한 시설이라고 답하였지만, 단점으로 높은 부상 위험성(71.1%)과 환경 유해 가능성(72.7%)을 각각 대답하였다. 교사와 직원은 맨땅운동장의 가장 큰 장점과 단점으로 자연과의 교감 환경 제공과 강우 시 사용 제한으로 같은 응답을 하였다. 마지막으로 교사와 직원이 차기 근무지에서 운동장을 조성한다고 가정할 때 선택하고 싶은 종류는 천연잔디>인조잔디>맨땅운동장 순서였다. 선택의 기준은 학생 안전, 환경에 대한 유해 정도, 관리의 난이도 등을 꼽았다. 무응답 중에는 학교 실정에 맞게 선택해야 한다는 의견도 있었다. There are three types (natural grass, artificial turf, and bare playgrounds) of school playgrounds in Korea. Knowing the thoughts of perception of students, teachers and staff, and student parent on the school playgrounds can be very important. However, no research has been done on the subject. This study is based on questionnaires received from 79 schools (27 natural grass, 23 artificial turf, and 29 bare playground schools) of 390 elementary, middle, and high schools where one of three types of playground is installed. The satisfaction of students, teachers and staff, and student parent according to the three types of school playground was in the order of natural grass>artificial turf>bare playground. Teachers and staff answered student safety (83.8%) and nature-friendly environment (90.9%), respectively, as the greatest advantages of a natural grass playground. They expressed different opinions by saying that the biggest disadvantage of natural grass playgrounds are limited use (71.1%) and difficult management (63.6%), respectively. Teachers and staff also answered that the most important advantage of artificial turf playground are available facilities throughout the year, but the biggest disadvantages are high injury risk (71.1%) and environmental hazard (72.7%). They responded with the greatest strength and weakness of the bare playground as the sympathy with nature and use restrictions during the rainy season. Assuming that they would set up a playground at their next workplace, the playground type they wanted to select was in the order of natural grass>artificial turf>bare playground. They answered that difficulty of playground management, student safety, and environmental risk are important as selection criteria. KCI Citation Count: 4